Puncak Pato Sebagai Destinasi Wisata Alam Sumatera Barat - Meria Eliza; Rosta Minawati; Syafriandi Syafriandi (Melayu Arts and Performance Journal, 2023)
Puncak Pato, West Sumatra, is a tourist destination located on the border of Sungayang and Lintau. Puncak Pato as a tourism destination has natural and cultural  potential. It also has historical meaning in Minangkabau for uniting indigenous peoples and religions known as the "Satie Marapalam Oath Agreement". Pato Peak (Bukit Marapalam) is the place where this  agreement was signed between the adat  and religious communities of Minangkabau. This research is a qualitative study that aims to provide a comprehensive and in-depth description of Puncak Pato as a tourist destination. Pato Peak is located in highlands surrounded by hills and pine trees. There is beautiful natural scenery with cool winds drawing many visitors from West Sumatra and  other areas. Existing tourist facilities encourage bicycling , jogging, gymnastics, with meeting places and sites for various cultural arts activities. The facilities also include a large parking area , prayer rooms, and rest rooms. Visitors to Pucak Pato need only buy an adult ticket of IDR 10,000, IDR 5000 for a child. . Visitors are further served by stalls selling food and beverages.Keywords: Puncak Pato; Nature Tourism; West SumateraAbstrakPuncak Pato Sumatera Barat merupakan destinasi wisata berlokasi di perbatasan Sungayang  dan  Lintau.  Objek  wisata Puncak Pato memiliki potensi wisata alam dan budaya dan juga memiliki nilai sejarah Minangkabau dalam menyatukan kaum adat dan kaum agama, yang dikenal dengan “ Perjanjian Sumpah Satie Marapalam”. Puncak Pato (Bukit Marapalam) merupakan tempat terjadinya suatu kesepakatan dan penandatanganan surat perjanjian antara kaum adat dan kaum agama di Minangkabau. Penelitian ini merupakan penelitian kualitatif yang bertujuan untuk memberikan gambaran yang menyeluruh  dan  mendalam  tentang  eksistensi  Puncak  Pato sebagai Destinasi Wisata. Puncak Pato terdapat di dataran tinggi dikelilingi bukit dan pohon pinus. Pemandangan alam yang indah dan tiupan angin yang memberikan kesejukan sehingga banyak pengunjung yang dari Sumatra Barat maupun dari daerah lainnya. Spot wisata yang ada diantaranya sepeda, joging, senam, tempat rapat dan kegiatan berbagai seni budaya. Fasilitas yang dimiliki adalah parkir yang luas, mushola, dan toilet. Untuk berkunjung ke Pucak Pato hanya dengan tiket dewasa Rp 10.000 dan anak Rp 5000. Untuk memanjakan pengunjung terdapat warung-warung penjual makanan dan minumanKata Kunci: Puncak Pato; Wisata Alam; Sumatera Barat